2011
DOI: 10.1007/s10840-011-9573-1
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of left atrial anatomical maps acquired with a multielectrode catheter during catheter ablation for atrial fibrillation

Abstract: Left atrial anatomical maps acquired using multielectrode catheters in conjunction with EAM are accurate and provide information regarding pulmonary vein dimensions and geometry which is similar to that obtained with CT/MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
0
15
0
2
Order By: Relevance
“…26 Thereafter, we divided the PVs and LA into 15 segments: the 4 PVs; the antra of each PV; the anterior, posterior, and septal surfaces and roof and floor of the LA; the mitral isthmus; and the LAA, as shown in Figure 1. The presence of EAT, high DF sites, and CFAE sites in the PVs and LA segments was assessed, and the correspondence between the EAT locations and the high DF and CFAE sites was quantified.…”
Section: Quantitative Assessment Of Distributions Of Eat High Df Sitmentioning
confidence: 99%
“…26 Thereafter, we divided the PVs and LA into 15 segments: the 4 PVs; the antra of each PV; the anterior, posterior, and septal surfaces and roof and floor of the LA; the mitral isthmus; and the LAA, as shown in Figure 1. The presence of EAT, high DF sites, and CFAE sites in the PVs and LA segments was assessed, and the correspondence between the EAT locations and the high DF and CFAE sites was quantified.…”
Section: Quantitative Assessment Of Distributions Of Eat High Df Sitmentioning
confidence: 99%
“…Because this was the first study investigating the clinical use of the new MBC, we enrolled only patients with right‐sided ATs to evaluate the safety of using the MBC. Previous studies have reported the utility of multielectrode catheters with NavX for activation mapping of left‐sided AT . In our opinion, rapid mapping with the new MBC might also be useful for understanding AT circuits in the left atrium.…”
Section: Discussionmentioning
confidence: 86%
“…Under fluoroscopic and intracardiac echocardiographic (ICE) (Acu Nav Diagnostic Ultrasound Catheter, Siemens Medical Systems, Issaquah, WA, USA) guidance, two trans‐septal punctures were performed via the right femoral vein, and 8 Fr SL1 (Daig St. Jude Medical) and 8.5‐Fr Agilis sheaths (St. Jude Medical) were advanced into the left atrium. Intravenous heparin bolus was given before the trans‐septal punctures and as a continuous infusion during the procedure with a goal activated clotting time of 300–350 seconds …”
Section: Methodsmentioning
confidence: 99%
“…Field scaling was employed for all electroanatomical maps created. The maps created with each method were then compared to preprocedural CT or MR scans of the LA and PVs, with measurements of the short‐ and long‐axis dimensions at the ostia of all four PVs, the distance between the ostia of the left superior PV and the right superior PV, the distance between the antra of the left inferior PV and the right inferior PV, and the width of the ridge separating the left superior PV from the LAA as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation